CORRELATIVE SEDIMENTARY MODEL OF UPPER JURASSIC REEF DEPOSITS IN PRECARPATHIAN AND PREDOBROGEAN REGIONS OF UKRAINE - Anikeyeva, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The correlative model of sedimentation of Upper Jurassic deposits in the Precarpathian and Predobrogean regions of Ukraine is presented. It is based on the model of sedimentation of Upper Jurassic–Valanginian deposits in Ukrainian Precarpathia according to the eustatic curve. The aim of the work was the detailed reconstruction and comparison of sedimentary conditions in different parts of paleobasin. Microfacies study of Upper Jurassic sediments, as well as analysis and synthesis of numerous literature data have been conducted. Two groups of factors that controlled these deposits formation are identified. Inter-regional factors include the eustatic fluctuations of the World Ocean, climate changes and global tectonic processes. Local factors include tectonic situation in the region, paleogeographic and paleoecological features in the part of paleobasin. The main stages (Oxfordian, Kimmeridgian and Tithonian–Berriassian) of the development of different parts of paleobasin are described. At the beginning of Oxfordian time, the normal marine, predominantly carbonate sedimentation associated with the birth and growth of reef constructions occured in Precarpathians and Predobrogea. In Predobrogea region, the relict Middle Jurassic river system in a significantly reduced form continued to exist during the Late Jurassic. Its influence on the processes of sedimentation increased in the Middle Oxfordian that predetermined a significant decrease of the area of carbonate sedimentation and forming the clay-terrigenous aluat suite in the western part of the region. A regression in the Late Oxfordian caused a considerable shallowing of the whole North-Tethyan basin and led to a local erosion of bioherms in Precarpathians and isolation of eastern part of the basin where there was an evaporite lagoon during the Early Kimmeridgian. In Predobrogea, due to local factors the reef system functioned until the Late Kimmeridgian. Since that time on all territory of Predobrogea, conditions have gradually changed from marine to lagoon and as a result the clastic-evaporite and halogen sequences have been formed. A transgression in the Late Kimmeridgian has resumed the marine environments all over the territory of Precarpathians where during the Tithonian-Berriasian there was a thick barrier reef, shallow coastal bioherms and also carbonate pre-reef and back-reef deposits were forming. This transgression has also restored a link with the sea in Predobrogea where lagoon-continental environments dominated. Tithonian marine sediments in this region were distributed locally and have been eroded almost completely.
Keywords: Upper Jurassic; sedimentary model; reefs; Precarpathians; Predobrogea